S109 The introduction of stereotactic ablative radiotherapy increases overall radical treatment rates for stage I lung cancer but does not reduce surgical resection rates–a two centre study. (14th November 2013) - Cheyne, L; Esterbrook, G; Viadyanathan, S; Milton, R; Smith, G; Blaxill, P; Clarke, K; Snee, M; Franks, K; Callister, MEJ
Abstract : Background: Stereotactic ablative radiotherapy (SABR) is a new treatment option for peripheral stage I lung cancer in patients unfit for surgical resection. SABR was introduced to Leeds Teaching Hospitals (LTHT) and Mid Yorkshire Hospitals (MYH) in May 2009. We sought to establish what effect the introduction of SABR had on surgical resection rates for stage I lung cancer, and compared clinical characteristics of patients receiving surgery, SABR, conventional radical radiotherapy (RRT) and best supportive care. Methods: All patients diagnosed with stage I lung cancer from 2008 to 2011 were analysed for treatment modality, performance status (PS) and lung function. Results: 565 stage I patients were studied and treatment rates over the 4 year period are shown below. The proportion of patients receiving SABR rates rose from 0% in 2008 to 26.1% in 2011. Surgical resection rates remained largely unchanged, but there was a reduction in the proportion of patients receiving best supportive care from 32.6% in 2008 to 13.7% in 2011. Overall radical treatment rates for the four years were 60%, 70.7%, 68% and 85% for 2008–2011 respectively. The proportion of patients with PS 0–1 were as follows: surgery 88%, SABR 39%, RRT 38% and BSC 13%. FEV1 (l) (mean% predicted, 95% CI) was significantly higher in patients receiving surgery (80.1, 77.3–82.9) compared to those patients receiving SABR (62.1, 56.0–68.3, p < 0.001 vs surgery), RRT (62.7, 54.2–71.3, p < 0.001 vs surgery) and BSC (56.4, 49.8–63.0, p < 0.001 vs surgery). Similarly gas transfer was significantly higher in the surgical patients compared to the other three groups. For stage I lung cancer patients over the age of 75, the proportion of patients SABR rose from 0% in 2008 to 32.1% in 2011. Overall numbers of patients aged over 75 receiving BSC decreased over the four years; 49%, 45.5%, 38.6% and 24.4% for 2008–2011 respectively. Conclusion: The introduction of SABR has led to a significant increase in overall radical treatment rates for patients with stage I lung cancer, without resulting in a sustained reduction in surgical resection rates. Patients undergoing SABR and RRT have worse lung function and performance status than those undergoing surgery.